Formulation, process, and storage strategies for lyophilizates of lipophilic nanoparticulate systems established based on the two models paliperidone palmitate and solid lipid nanoparticles - Trenkenschuh, Eduard; Savsek, Ula; Friess, Wolfgang (International Journal of Pharmaceutics, 2021)
Lyophilization formulation and process development for lipophilic nanoparticle (NPs) products is highly challenging as the NPs have a low colloidal stability. We compared two different NP types, pure paliperidone palmitate nanocrystals and trimyristin solid lipid nanoparticles regarding formulation, process, and storage stability aspects. Freeze-thaw studies were conducted to investigate the basic formulation aspects such as buffer type, pH, and ionic strength as well as different cryoprotectants. In freeze-drying conventional ramp freezing was performed and compared to freezing with an annealing step added or with controlled ice nucleation. Different formulations were lyophilized and tested for short-term storage stability up to 6 weeks. Samples were analyzed for particle size, subvisible particle number, specific surface area, residual moisture, crystallinity, and glass transition temperature. Sucrose significantly better stabilized both NP types against freeze-thaw stress compared to mannitol demonstrating the importance of a fully amorphous matrix. While the impact of buffer type and pH was negligible, the aggregation propensity of NPs was reduced in presence of NaCl. The freezing step also impacted NP aggregation but the effect was less important than the formulation design. Surfactants did not necessarily improve the colloidal stability but resulted in a lower glass transition temperature of the lyophilizates and may cause phase separation which limits storage stability. This hurdle can be overcome by using a hydroxypropyl-beta-cyclodextrin/ sucrose mixture as cryoprotectant. In general, we could show a similar freeze-drying behavior of the two NP types. Thus, we established a formulation and process approach to achieve stable lyophilizates of lipophilic NPs based on two different types of NPs. The general rules should be transferable to other NPs facilitating lyophilization development.
CRIS-Team WoS Importer:2021-09-10